Development of automatic conveying system for vegetable seedlings - Xin Jin (EURASIP Journal on Wireless Communications and Networking, 2018)
Abstract In order to improve the automation and reliability of the mechanized transplanting, a vegetable seedling automatic conveying system was designed. The functional execution component of the system consists of a tank-wheel storage seedling mechanism, a seedling tray conveyor, and a hanging cup circulating conveying mechanism. Combined with the communication technology between host computer and programmable logic controller (PLC), the user interface software of automatic conveying system for potted vegetable was developed by using Visual Studio to control and monitor the transmission progress. The PVDF pressure sensor was used to detect the pressure change of the seedling storage disk to obtain the information of the loading seedling tray. The limit switch and stroke switch were combined to obtain the information of the push rod and feed plate. The timing of each component is controlled by the PLC controller combined with the feedback information of each sensor. The test results show the effect of taking an individual seedling is excellent, the error rate of the pushing mechanism is about 2.08%, and the success rate was 97.91%.